Pengaruh Citra Merek, Harga Dan Kualitas Produk Terhadap Loyalitas Pelanggan keripik Megasari Cipongkor - Shandy Aditia Miharja; Nurhayati (CV. Ulil Albab Corp, 2024)
The purpose of this study was to understand how Brand Image, Price, and Product Quality affect Customer Loyalty of Megasari Chips in Cipongkor District. This research uses a quantitative approach with data collection through a Google Form questionnaire and uses a Likert scale from 1 to 5. The data was analyzed using SPSS version 27 with the normality test method, multiple linear regression test, F test, t test, correlation coefficient and determination. The research sample consisted of 100 respondents in Cipongkor who had purchased Megasari Chips at least twice. Simultaneously, Brand Image, Price, and Product Quality have a significant influence on Customer Loyalty of Megasari Chips. Partially, Brand Image and Price do not show a significant effect, while Product Quality is proven to have a positive and significant effect on Customer Loyalty of Megasari Chips. These findings emphasize the importance of improving Product Quality as the main strategy to increase customer loyalty. This research makes an important contribution in designing more effective marketing strategies for Megasari Chips products.